PERBEDAAN JUMLAH HITUNG FOLIKEL ANTRAL PADA PENGGUNA KONTRASEPSI HORMONAL DAN NON HORMONAL DI RUMAH SAKIT Dr. M DJAMIL PADANG - Lasmini, Putri Sri; Machmud, Rizanda (Andalas Obstetrics And Gynecology Journal, 2017)
It remains controversial whether antral follicle count is influenced by hormonal contraception.. This study quan-tified the effect of hormonal contraception on sonographic ovarian reserve markers in 32 users and 32 non-users of hormonal contraception. This was a prospective clinical trial study and has been performed in gynecology Department of M. Djamil Hospital Padang, primary health care March to July 2014. Samples then divided into two groups, group A was users of non hormonal contraception and group B was users of hormonal contraception. On day 2–4 of the menstrual cycle transvaginal sonography was performed and measured repeatedly in the same individual before and after the use of one cycle oral contraceptives (for group B), and on first month and second month (for group A). Statistical analysis to assess significance using the unpaired t test and chi square on SPSS 18.0 for windows. There was no significant association of the antral follicle count between users than non-users of hormonal contraception (p>0,05). There were no significant difference of antral follicle count between users and non- users of hormonal contraception. There were no significant difference of gain score of antral follicle count between users and non-users of hormonal contraception.Keywords: Antral Follicle Count, Users Of Hormonal Contraception, Non-Users Of Hormonal Contraception